1991
DOI: 10.1111/j.2044-8295.1991.tb02409.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in cognitive processes: Towards an explanation of schizophrenic symptomatology

Abstract: A study is reported that examined the relationship between a measure of schizophrenic-like characteristics (schizotypy) in normal subjects and cognitive inhibition. Both repetitive and semantic measures of priming were used. It was found that low schizotypes showed negative priming (i.e. longer reaction times to the re-presentation of initially ignored stimuli) while high schizotypes did not; high schizotypes exhibited semantic facilitation (i.e. shorter reaction times to previously ignored stimuli) but low sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 14 publications
6
59
0
Order By: Relevance
“…For example, Beech, Powell, McWilliam, and Claridge (1989) found that people with schizophrenia show diminished NP in comparison with a group of matched controls. Furthermore, university students who obtain high scores on questionnaire measures of schizophreniclike symptoms tend to show increased flanker interference from ignored distractors, but reduced NP relative to those with low scores on the same questionnaires Beech & Claridge, 1987;Beech et al, 1991). Once again, it should be noted that these results may indicate problems with retrieval mechanisms rather than with inhibitory mechanisms.…”
Section: Individual Differences In Negative Primingmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, Beech, Powell, McWilliam, and Claridge (1989) found that people with schizophrenia show diminished NP in comparison with a group of matched controls. Furthermore, university students who obtain high scores on questionnaire measures of schizophreniclike symptoms tend to show increased flanker interference from ignored distractors, but reduced NP relative to those with low scores on the same questionnaires Beech & Claridge, 1987;Beech et al, 1991). Once again, it should be noted that these results may indicate problems with retrieval mechanisms rather than with inhibitory mechanisms.…”
Section: Individual Differences In Negative Primingmentioning
confidence: 77%
“…Several individual-difference studies have indeed found evidence for such an inverse relation between flanker interference and NP. To illustrate, Beech and his colleagues (Beech, Baylis, Smithson, & Claridge, 1989;Beech & Claridge, 1987;Beech, McManus, Baylis, Tipper, & Agar, 1991;Beech, Powell, MeWilliam, & Claridge, 1989) have demonstrated that subjects with high schizotypical personality traits are more susceptible to flanker interference from ignored distractors and also show less NP from the same distractors. A very similar pattern has been found both for older adultswho tend to show heightened distractibility and reduced NP relative to younger adults (Hasher et aI., 1991;Tipper, 1991)-as well as for young children (Tipper et aI., 1989).…”
Section: Negative Priming 159mentioning
confidence: 99%
“…When evidence for the inhibition of distractor identity is sought, researchers have mainly used identification tasks (Driver & Baylis, 1993;Driver & Tipper, 1989;Fuentes & Humphreys, 1996). To obtain evidence for the inhibition of central/semantic representations of distractors, categorization and naming tasks are preferred (Beech, McManus, Baylis, Tipper, & Agar, 1991;Tipper & Baylis, 1987;Tipper & Driver, 1988). To examine negative priming from locations, participants are asked to perform a localization task in the prime (Milliken, Tipper, & Weaver, 1994).1…”
Section: Mechanisms Of Distractor Inhibitionmentioning
confidence: 99%
“…Such studies can examine the relationship between schizotypal syndromes and NP in the absence of medication. There is considerable evidence supporting reduction of verbal NP effect in schizotypal individuals especially when positive syndromes are present (Beech & Claridge, 1987;Beech, McManus, Baylis, Tipper, & Agar, 1991;Beech et al, 1989;Moritz, Mass, & Junk, 1998). But Sturgill & Ferraro, (1997) found that deficits in verbal NP was correlated with elevated schizotypal traits.…”
Section: Review Of the Negative Priming Effect In Schizophrenia And Smentioning
confidence: 99%
“…Studies of schizotypal personality have shown that spatial NP is reduced in unmedicated schizotypal individuals, especially among those with elevated positive syndromes (e.g., Beech et al, 1991;Moritz et al, 1998;Park et al, 1996;Watson & Tipper, 1997).…”
Section: Review Of the Negative Priming Effect In Schizophrenia And Smentioning
confidence: 99%